A review on tensegrity structures-based robots. (February 2022) - Liu, Yixiang; Bi, Qing; Yue, Xiaoming; Wu, Jiang; Yang, Bin; Li, Yibin
Abstract: Human-robot coexistence has become an important trend of the new generation of robots. Both rigid structures and soft structures have their own limitations in certain application scenarios. The tensegrity structure, which is widely used in the field of architecture and structural engineering, is a self-supporting and self-stressed spatial grid structure composed of discrete compression elements and continuous tension elements. This kind of structure combines the advantages of rigid structures and soft structures, and conforms to the natural evolutionary laws of creatures, providing helpful inspirations for the research of the new generation of robots. Tensegrity structures are being more and more widely used in robotics. The objective of this paper is to review the state-of-the-art of tensegrity structures-based robots and analyze the key techniques in aspects of design and fabrication, modeling and analysis, motion and controlling. Possible future applications of tensegrity robots are also prospected. Although there are still few actual applications in practice, tensegrity structures-based robots, as a unique rigid-flexible coupling structure, have great potentials in the future. Highlights: The state-of-the-art of tensegrity robots is reviewed for the first time. The key techniques of tensegrity robots are analyzed. Future possible applications of tensegrity robots are prospected. Tensegrity robots have great potential in the future.